Enhanced N-V interaction domains for the design of CLT shear wall based on coupled connections models. (15th March 2021) - Franco, Luca; Pozza, Luca; Saetta, Anna; Talledo, Diego
Highlights: Simplified methodology for the seismic design of CLT wall systems. Evaluation of N-V interaction domains for CLT wall systems. Axial-shear coupling of connections used in CLT wall systems. Abstract: The present paper proposes some enhanced models, with different levels of accuracy, for the design of monolithic CLT shear wall based on the definition of reliable N-V interaction domain. The basic assumptions and the novelty aspects of the proposed models are presented. In particular, the adoption of an elastic-perfectly-plastic constitutive law for the timber instead of an elasto-brittle one and the accounting for the coupled axial-shear behavior of the connection elements to derive N-V interaction domains are critically discussed. Moreover, two different methods are adopted for the linearization procedure of the connection load-displacement response. Four of the proposed models are design oriented, two representing a lower bound (more suitable for practitioners), and two representing an upper bound. One more model is developed, which is research oriented and based on hybrid force-displacement approach. The reliability of the different models is investigated by means of numerical analyses exploiting the ultimate failure condition of the materials both in terms of strength and displacement capacity. Finally, the N-V domains for some CLT shear walls are presented and the impact of the different basic assumptions on the results are discussed in comparison with both experimental and numerical literature results.